Analisis Kebijakan Fiskal terhadap Pertumbuhan Ekonomi di Indonesia - Dian Novita Sari; Rouzatul Jannah; Yani Rizal; Puti Andiny; Safuridar Safuridar (Jurnal Riset Ekonomi dan Akuntansi, 2024)
Fiscal policy is one of the main instruments used by the government to manage the economy. This research aims to analyze the fiscal policy on economic growth in Indonesia, focusing on domestic tax revenue, foreign tax revenue, and export taxes. The method used in this research is multiple linear regression. The data utilized consists of time series data from 2010-2023, sourced from official institutions such as the Central Statistics Agency (BPS) of Indonesia. The results of this study indicate that, simultaneously, domestic tax revenue, foreign tax revenue, and export taxes have a significant impact on economic growth in Indonesia. Meanwhile, on a partial basis, it shows that tax revenue has a positive and significant effect, non-tax revenue has a positive but insignificant effect, and export taxes have a negative and insignificant effect on economic growth in Indonesia.